Analisis Sistem Pengawasan Hakim Dalam Mewujudkan Peradilan Yang Akuntabel - Arifin Tumuhulawa; Ferari D. Susilo; Ramdan Kasim (Jurnal Hukum Bisnis, 2024)
This study aims to examine and analyze the system of supervision and supervision of judges to realize an accountable judiciary. Research Methods Based on the research focus, this type of research is classified as normative legal research. Normative legal research is "a process rules to find a rule of law, legal principles, and legal doctrines to answer the legal issue at hand. The results showed that the judicial mafia that is endemic in the judicial power environment cannot be separated from the weakness of an institution's internal supervision system, the unconsolidation of internal and external supervision systems, the non-integration of inherent supervision and functional supervision, the non-accommodation of public participation through handling claims and complaints as well as the contribution of ideas and ideas to participate in maintaining dignity and respect Judicial power, weak character and integrity of judges and institutional leadership elements and still closed operational systems and procedures for the implementation of judicial power. With effective supervision, it can be ensured that judges carry out their duties by applicable ethical and legal standards.